Before I die - Chang, Candy (St. Martin's Griffin, 2013)
"When artist Candy Chang painted the side of an abandoned building with chalkboard paint and the wrote the words, "Before I die, I want to ____ ," she never expected it to become a worldwide phenomenon. Within a day of the wall's completion, however, it was covered in colorful chalk dreams as people stopped and reflected on their lives. Since then, more than two hundred walls have been created by people all over the world. This inspiring book is a celebration of these walls. Filled with our hopes, fears, humor, and heartbreak, it's a reminder of our shared connections and a chance to contemplate life's most important question" --